1993
DOI: 10.1002/1098-108x(199312)14:4<515::aid-eat2260140417>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention to food and body shape words in dieters and restrained nondieters

Abstract: The current study investigated the presence of an attentional bias towards the processing of body shape and food‐related material amongst noneating disordered women. Subjects carried out a computer‐based Stroop color‐naming task in which they had to name the colors of food‐related words, body shape‐related words, and two sets of matched neutral words. Significant color‐naming disruptions of both food and body shape‐related material were found for highly restrained eaters, irrespective of whether they were curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 8 publications
(9 reference statements)
5
56
0
Order By: Relevance
“…Participants with eating disorders consistently exhibit attentional bias when processing diet and body-shape-related words (Dobson & Dozois, 2004) so it seems reasonable to suggest that the same may be true of obese and dieting participants (Green & Rogers, 1993), for whom these words are also resonant.…”
Section: Methodssupporting
confidence: 92%
“…Participants with eating disorders consistently exhibit attentional bias when processing diet and body-shape-related words (Dobson & Dozois, 2004) so it seems reasonable to suggest that the same may be true of obese and dieting participants (Green & Rogers, 1993), for whom these words are also resonant.…”
Section: Methodssupporting
confidence: 92%
“…Previous research using the modified Stroop task has found that restrained eaters display a general attentional bias for food cues (Francis et al, 1997;Green & Rogers, 1993;Overduin et al, 1995;Perpina et al, 1993;Stewart & Samoluk, 1997). …”
Section: Discussionmentioning
confidence: 73%
“…The difference in reaction times for the food in neutral and the neutral in neutral matrix types was greater for restrained than for unrestrained eaters. This result shows that restrained eaters display an enhanced orientation of attention toward food cues, supporting interpretations of a heightened vigilance for food cues found in Attentional bias and dietary restraint 12 previous studies using other methodologies such as the Stroop task (Francis et al, 1997;Green & Rogers, 1993;Overduin et al, 1995;Perpina et al, 1993;Stewart & Samoluk, 1997). Most likely because of their preoccupation with food (Cogan & Ernsberger, 1999;Polivy & Herman, 2002), restrained eaters' attention is more readily captured by environmental food cues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations